Positive and Detached Reappraisal of Threatening Music in Younger and Older Adults - Vieillard, Sandrine; Pinabiaux, Charlotte; Bigand, Emmanuel (Frontiers in Human Neuroscience, 2020)
Past empirical studies have suggested that older adults preferentially use gaze-based mood regulation to lessen their negative experiences while watching emotional scene. This preference for low cognitively demanding regulatory strategy leaves open the question of whether the effortful processing of a more cognitively demanding reappraisal task is really spared from the general age-related decline. Because it does not allow perceptual attention to be redirected away from the emotional source, music provides an ideal way to address this question. The goal of our study was to examine the affective, behavioral, physiological and cognitive outcomes of positive and detached reappraisal in response to negative musical emotion in younger and older adults. Participants first simply listened to a series of threatening musical excerpts and were then instructed to either positively reappraise or to detach themselves from the emotion elicited by music. Findings showed that when instructed to simply listen to threatening music, older adults reported a more positive feeling associated with a smaller SCL in comparison with their younger counterparts. When implementing positive and detached reappraisal, participants showed more positive and more aroused emotional experiences, whatever the age group. We also found that the instruction to intentionally reappraise negative emotions results on a lesser cognitive cost for older adults in comparison with younger adults. Taken together, these data suggest that compared to younger adults, older adults engage in spontaneous down-regulation of negative affect and successfully implement down-regulation instructions. This extends previous findings and brings compelling evidence that even when auditory attention cannot be redirected away from the emotional source, older adults are still more effective at regulating emotions. Taking into account the age-associated decline in executive functioning, our results suggest that the working memory task could have distracted older adults from the reminiscences of the threatening-evoking music, thus resulting in an emotional down-regulation. Hence, even if they were instructed to implement reappraisal strategies, older adults might prefer distraction over engagement in reappraisal. This is congruent with the idea that while getting older, people are more likely to be distracted from a negative source of emotion to maintain their wellbeing.